IMF Staff papers : Volume 16 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1969)
This paper shows how to utilize the data on trade structure to achieve the best possible estimates of the effects of price changes, given any reasonable array of elasticity estimates. The credibility of estimates of price effects depends on thorough and systematic use of these data, as well as on the statistical credentials of the elasticities assumed. The observations show that the impact of a given price change on a country's exports will be greater, the more that country's exports are concentrated in markets in which substitution elasticities are high, and vice versa, but for most countries strong correlations of this kind are not probable. The general conclusion to be drawn from the paper would seem to be that the information implicit in the base-period matrix is not enough to yield results in which a high degree of confidence can be placed. It remains essential to employ substitution elasticities that are supported by the historical record. Nevertheless, the role of trade structure is vitally important.